2014
DOI: 10.1590/s0034-8910.2014048005278
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to breastfeeding in the first hour of life: systematic review

Abstract: OBJECTIVE To identify independent risk factors for non-breastfeeding within the first hour of life.METHODS A systematic review of Medline, LILACS, Scopus, and Web of Science electronic databases, till August 30, 2013, was performed without restrictions on language or date of publishing. Studies that used regression models and provided adjusted measures of association were included. Studies in which the regression model was not specified or those based on specific populations regarding age or the presence of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
124
3
26

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(170 citation statements)
references
References 55 publications
17
124
3
26
Order By: Relevance
“…Also, mothers who delivered vaginally had a higher prevalence of early breastfeeding within the first hour (20.7% versus 1.1%). This finding was observed also by several studies (6,28,34,44,45,46). The rate of caesarean sections in our study (40.2%) was much higher than that reported previously in KSA (9.9 -13%) (26,47).…”
Section: Discussion:-supporting
confidence: 85%
See 1 more Smart Citation
“…Also, mothers who delivered vaginally had a higher prevalence of early breastfeeding within the first hour (20.7% versus 1.1%). This finding was observed also by several studies (6,28,34,44,45,46). The rate of caesarean sections in our study (40.2%) was much higher than that reported previously in KSA (9.9 -13%) (26,47).…”
Section: Discussion:-supporting
confidence: 85%
“…Similarly, other studies reported a lack of association between demographic factors and infant's gender (28,42,43). In a systematic review of 18 research studies from Asia, Africa and South America, neither the age of the mother nor other factors such as 1069 family income or schooling were found to be independent risk factors preventing breastfeeding within the first hour of life (44). However, other studies have reported a significant association between increased maternal age (34), parity (34), the infant's gender (6) and initiation of breastfeeding within 24 hours post delivery.…”
Section: Discussion:-mentioning
confidence: 96%
“…Finally, the mothers' factors included the education level, age at the child's birth, hospital delivery status and number of postpartum visits, as well as whether the mother cooked for the child alone and was given informational breast-feeding materials. We selected the control variables based on the following considerations: (i) whether these aforementioned factors affected the breastfeeding of the children (a factor that was primarily based on related studies (5)(6)(7)(8)(9)(10) ); and (ii) how these variables differed between the participants across ethnicities, which was determined by data analysis.…”
Section: Control Variablesmentioning
confidence: 99%
“…In addition to its immunological and bioactive importance, colostrum has epidermal growth factors, which contribute to the maturation of the intestinal mucosa, hence preventing intestinal colonization by disease-causing microbes [17].…”
Section: Discussionmentioning
confidence: 99%